Variability in the prevalence of adult ADHD in treatment seeking substance use disorder patients: Results from an international multi-center study exploring DSM-IV and DSM-5 criteria - Van de Glind, G.; Konstenius, Maija; Koeter, Maarten; Van Emmerik-Van Oortmerssen, Katelijne; Carpentier, Pieter; Kaye, Sharlene; Degenhardt, Louisa; Skutle, Arvid; Franck, Johan; Bu, Eli-torild; Moggi, Franz; Dom, Geert; et al. (Elsevier Ireland Ltd, 2014)
Attention deficit/hyperactivity disorder (ADHD) is an increasingly recognized comorbid condition in subjects with substance use disorders (SUDs).This paper describes the methods and study population of the International ADHD in Substance Use Disorders Prevalence (IASP) study. Objectives of the IASP are to determine the prevalence of ADHD in adult treatment seeking patients with SUD in different countries and SUD populations, determine their liability and validity of the Adult ADHD Self-report Scale V 1.1 (ASRS) as ADHD screening instrument in SUD populations, investigate the comorbidity profile of SUD patients with and without ADHD, compare risk factors and protective factors in SUD patients with and without a comorbid diagnosis of ADHD, and increase our knowledge about the relationship between ADHD and the onset and course of SUD. In this cross-sectional, multi-centre two stage study, subjects were screened for ADHD with the ASRS, diagnosed with the Conner’s Adult ADHD Diagnostic Interview for DSM-IV (CAADID), and evaluated for SUD, major depression, bipolar disorder, anti-social personality disorder and borderline personality disorder. Three thousand five hundred and fifty-eight subjects from 10 countries were included. Of these 40.9% screened positive for ADHD. This is the largest international study on this population evaluating ADHD and comorbid disorders.